Imaging Modalities for Correct Positioning of Percutaneous Right Ventricular Assist Device After Left Ventricular Assist Device Implantation. Issue 5 (1st March 2018) - Geube, Mariya A.; Alfirevic, Andrej; Tong, Michael
Abstract : Supplemental Digital Content is available in the text.